1968
DOI: 10.1039/j19680003051
|View full text |Cite
|
Sign up to set email alerts
|

Prototropic equilibria of electronically excited molecules. Part II. 3-, 6-, and 7-Hydroxyquinoline

Abstract: The absorption and the emission spectra of the four ionic species formed by 3-, 6-, and 7-hydroxyquinoline in aqueous solution have been measured, and the constants governing the prototropic equilibria between the ionic forms of each compound in the lowest singlet excited state have been estimated theoretically from the transition energies and experimentally from the change in fluorescence spectrum with hydrogen-ion concentration. It is found that the phenolic group of the hydroxyquinolines is more acidic, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
177
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(186 citation statements)
references
References 0 publications
7
177
0
2
Order By: Relevance
“…They explained that the fluorescence is forbidden due to symmetry. However, with the same symmetry, the fluorescence from both the cationic and anionic forms of 6HQ have been observed in emission spectra [37,39]. Meanwhile, by using CASSCF and CASPT2 calculations without symmetry constraints, Serrano-Andrés and co-workers suggested that [43], ESMPT would be preferred over hydrogen-atom transfer in the excited-state tautomerization of 7HQÁ(NH 3 ) 3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They explained that the fluorescence is forbidden due to symmetry. However, with the same symmetry, the fluorescence from both the cationic and anionic forms of 6HQ have been observed in emission spectra [37,39]. Meanwhile, by using CASSCF and CASPT2 calculations without symmetry constraints, Serrano-Andrés and co-workers suggested that [43], ESMPT would be preferred over hydrogen-atom transfer in the excited-state tautomerization of 7HQÁ(NH 3 ) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…And the resulting ketonic form (8KQ) is supposed to be barely emissive [35]. On the other hand, the hydrogen-bonded wire can be hardly formed in 6-hydroxyquinoline (6HQ) [37][38][39], which requires an extreme long bridge to connect the functional groups. We believe that, the hydrogen-bonded wire with two or three components (H 2 O, NH 3 or alcohols, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13] For example, the dielectric constant of a water nanopool has been reported to be much lower than that of bulk water (ε = 78. 5) 17 but similar to that of an alcohol (ε = [30][31][32][33][34][35][36][37][38][39][40]. 18,19 On the other hand, biological processes often take place based on proton relay along a hydrogen (H)-bonded chain, [1][2][3][4][20][21][22][23][24] and the dynamics of biological proton relay is determined by the size, the structure, and the motion of a water cluster which is the prime agent in most of biological systems.…”
Section: -16mentioning
confidence: 99%
“…[13][14][15][16][35][36][37][38][39][40][41][42][43][44] On one hand, a 7-hydroxyquinoline molecule can form a cyclically H-bonded complex with two protic solvent molecules such as water and alcohols, so that proton relay from the enolic group to the imino group of 7-hydroxyquinoline occurs along a H-bonded solvent chain in a concerted fashion. 15,16,[42][43][44] On the other hand, those two prototropic groups of 6-hydroxyquinoline (6HQ) are too far from each other to form a cyclic complex with solvent molecules, so that proton transfer from the enolic group to the imino group of 6HQ takes place in a stepwise manner via accumulating cationic or anionic intermediate species.…”
Section: Notesmentioning
confidence: 99%